Nuclear techniques to investigate source and origin of groundwater pollutants and their flow path at Indian Rare Earths Ltd., Cochin, Kerala - K. Tirumalesh, K. Shivanna, J. Noble, K. K. Narayan, K. T. Xavier (Journal of Radioanalytical and Nuclear Chemistry, Vol. 274, No.2 (2007) 307-313, 2007)
Hydrochemical, environmental isotope and injected radiotracer investigations were carried out in order to investigate the possible source of contaminants and their movement in groundwater at Indian Rare Earths (IRE) site. Water samples were collected from piezometers, dug wells and river in and around IRE site for measurement of physical parameters, chemistry and isotopes. Chemical results show high fluoride, nitrate, sulphate and phosphate concentrations in piezometers whereas dug wells and river samples are free from contamination. Isotope data indicate that the contaminated groundwaters are enriched in ..2H and ..18O compared to dug well and river samples. radiotracer experiments were carried out using single-well and multi-well techniques (radiotracers: 82Br and 3H) for determining groundwater filtration velocity and flow direction, respectively. Groundwater filtration velocity was found to be about 1.3 cm/day and flow direction is from south to north. Based on the investigations it can be concluded that groundwater is getting contamination from southern part of IRE campus and the possible source for these contaminants could be the Fertilizer and Chemical of Travancore (FACT) industry